AN ANALYSIS OF SATIRICAL EXPRESSION USED IN THE 2024 WEST SUMATRA GUBERNATORIAL DEBATE - Prastiwi, Nadhira Dwi; Azhari, Andry (LINGUA LITERA : journal of english linguistics and literature, 2025)
Satire is an expression or sentence used to indirectly mock someone or something. This study aims to find out the types of satirical expressions used in the 2024 West Sumatra Gubernatorial Debate. This is due to the fact that the opponents of the West Sumatra Gubernatorial Debate often used satirical expressions during the debate session. The satire utterances were classified based on the theory of Abrams and Harpham (2015), which divides satire into two types: direct (Horatian and Juvenalian) and indirect (Menippean). This study was qualitative descriptive and collected the data by using non-participant observation. The data were analyzed using the intralingual padan method, which involves form testing and context testing. The data were taken from the transcription of the 2024 West Sumatra Gubernatorial Debate. The debate for the election was held twice. This research found all types of satire in the 2024 West Sumatra Gubernatorial Debate. There are 47 data of satire which 17 categorized as Horatian, 25 categorized as Juvenalian, and 5 categorized as Menippean satire. These findings indicate that satire functioned not only as a rhetorical strategy but also as a form of verbal attack in the context of political campaigns and also to undermine opponents' capabilities.